The Employee Performance Analysis: The Role of Organizational Culture and Job Satisfaction - Premesti, Ajeng Dwipa; Yuniningsih, Yuniningsih (Manunggal Halim Jaya, 2023)
All agencies want to get maximum results to achieve company targets and goals. Therefore, many companies must make efforts, one of which is by making improvements to human resources. In the current era of globalization, competition between human resources is increasing and competitive. This study discusses the analysis of employee performance. Analysis of the existence of organizational culture and job satisfaction on employee performance is the purpose of this research. The population in this study were all employees totaling 30 employees. Sampling is carried out on all members of the population that is used as a sample, which is called the saturated sampling technique. The number of 30 respondents who are employees. The data collection methods is questionnaires and observation. The analytical test tool used is SmartPLS 3.3.9 with the Partial Least Square method. In this study, the R-Square value was 60.2%. It has been concluded that in this study organizational culture has a positive influence and job satisfaction has a positive influence on employee performance.